Using the Gun of Mathematical Induction to Conquer Some Theorems of The Mulatu Numbers. - Patel, Dhruvika; Lemma, Mulatu (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2017)
The Mulatu numbers are sequences of numbers of the form 4, 1, 5, 6, 11, 17, 28, 45, .... Thenumbers have wonderful and amazing properties and patterns. In mathematical terms, it is defined by the following recurrence relation: The first number of the sequence is 4, the second number is 1, and each subsequent number is equal to the sum of the previous two numbers of the sequence itself. That is, after two starting values, each number is the sum of the two preceding numbers. In this paper, we give summary of some important properties and patterns of Mulatu numbers. Its relations to the Fibonacci and Lucas numbers are also investigated.